2022
DOI: 10.1021/acsami.2c18559
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polymer Template for Low-Cost Producing High-Performance Ti3C2Tx MXene Electrodes for Flexible Supercapacitors

Abstract: MXenes, two-dimensional (2D) transition-metal carbides and nitrides with high electrical conductivity, show outstanding potential for energy storage applications. However, the aggregation and restacking of 2D MXene nanosheets seriously decrease the performance of MXene-based electrodes. Instead of using high-cost artificial templates, herein, we select natural rubber (NR) latex-containing uniform sub-macroparticles as sacrificial templates and successfully construct three-dimensional interconnected porous MXen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…[46] In contrast, NRL exhibits a significant weight loss phenomenon at 400 °C. [47] By measuring the weight percentage at around 450 °C, we confirmed the weight ration of PEDOT:PSS and NRL in the composite matches the desired ratio, which also proven the uniform mixing of the composite ink.…”
Section: Resultssupporting
confidence: 57%
“…[46] In contrast, NRL exhibits a significant weight loss phenomenon at 400 °C. [47] By measuring the weight percentage at around 450 °C, we confirmed the weight ration of PEDOT:PSS and NRL in the composite matches the desired ratio, which also proven the uniform mixing of the composite ink.…”
Section: Resultssupporting
confidence: 57%
“…As shown in Figure S1b , MoS 2 is made of multiple layers with a thickness of about 4.5~53.4 nm. According to the thickness of single-layer MoS 2 reported in the literature (~0.65 nm) [ 34 ], it can be estimated that there are about 7~80 layers stacked, which consists of the data obtained by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…S8, ESI †) showed that the (002) peak of Ti 3 AlC 2 at around 101 was shifted to 6.301 in Ti 3 C 2 with increased lattice parameters, suggesting the increased layer space in Ti 3 C 2 after the etching process, and the XRD pattern of Ti 3 C 2 (in agreement with previous reports) demonstrated the successful fabrication of the Ti 3 C 2 nanosheets. 25,27,49…”
Section: Synthesis and Characterization Of Ti 3 C 2 Nanosheetsmentioning
confidence: 99%
“…26 As described previously, Ti 3 C 2 tended to agglomerate due to the high surface energy and van der Waals forces, which impaired its electrochemical performance. 49,66 Inspired by the combination between the nanoparticles and hydrogel, 67 Ti 3 C 2 nanosheets were involved in the bioinks through the 3D printing and coating method to detect the influence of different methods of modification on the photothermal properties. Composite scaffolds were modified with the same content ratio of Ti 3 C 2 through the coating process and 3D printing process, which were named MX@BS and BMS, respectively (Fig.…”
Section: In Vitro Photothermal Performancementioning
confidence: 99%